Pedagogic videos as a foreign language learning resource in textbooks used in the German studies section of a South African university: A digital multimodal discourse perspective - Schafli, Sasha-Lee (Rhodes University, Faculty of Humanities, Department of Linguistics and Applied Language Studies)
Video is a prominent teaching and learning tool within foreign language (FL) textbook media packages in the 21st century. While studies undertaken in the Global North highlight that video materials in the FL classroom have the potential to influence learning and cultural knowledge acquisition, there is a lack of research on the manner in which pedagogically designed videos influence adult FL learning and cultural knowledge acquisition in a South African context. In this study, I explore the opportunities and challenges in terms of language learning and cultural knowledge acquisition that arise from three pedagogic videos in the Menschen A1 textbook which is used in teaching students registered for the German Studies 1 course at Rhodes University. I compare and contrast two sets of data to examine the relationship between pedagogic video and student knowledge acquisition: the results of a digital multimodal discourse analysis (DMDA) of these videos, and questionnaires and transcriptions collected from semi-structured group interviews with German Studies 1 students. These questionnaires and transcriptions were analysed thematically. Findings in terms of the language learning experience indicate that actor over-exaggeration and visual aids assist students when learning German at this level with this type of video. However, these visual aids can be distracting and confusing without balanced representation and contextual information. Differences between videos in terms of speech rate seem to affect students' perceptions of their ability to comprehend the videos. Students reported forming only positive impressions of German culture(s) on the basis of the videos. In general, students find Germans portrayed as friendly and helpful in the videos. The results of this investigation provide recommendations for the optimal use of this type of teaching and learning resource, for example, teachers/ lecturers/ facilitators should allow for focus group discussions on cultural discourse to occur in order to balance stereotype formation and should consider the speech rate of videos for language learning.
Keywords: Language and languages-- Study and teaching Audio-visual aids; Educational technology; Media programs (Education); German language-- Study and teaching Foreign speakers Audio-visual aids; Visual learning; Rhodes University; German language Discourse analysis; Digital multimodal discourse analysis